Physical properties of dust resulting from cutting some building materials in Baghdad city - Oraibi, Hajer Ali; Fleeh , Nada Abdul Rahman (University of Thi-Qar Journal of Science, 2025)
From a toxicological perspective, particles with diameters less than 10 micrometers are referred to as inhalable particles. These particles possess the capability to penetrate deeply into the respiratory system, resulting in severe health consequences such as lung and respiratory diseases. Exposure to suspended particles has been associated with mortality, heart conditions, and respiratory ailments, particularly among children and the elderly. the study extended over the period of work from September 2022 to February 2023. two construction sites were conducted, each of the construction sites is located in Baghdad. According to the suggested national ambient air quality standards in Iraq (Profile on Environmental and Social Considerations in Iraq 2011) all the average values for PM2.5 exceed the World Health Organization (15μg/m3) and the Iraqi limit standard (35 μg/m3). PM10 also exceeds the standard limits of WHO (45 μg/m3) and the Iraqi limits (150 μg/m3) The study on Iraqi tile and marble dust particle diameters as physical properties provides valuable insights into the characteristics of these materials. By analyzing the particle sizes, researchers gain a deeper understanding of their behavior, dispersion, and potential applications. The investigation involves some measurements and statistical analysis to establish correlations between particle dimensions and its health impact on tile setters.